2017
DOI: 10.1021/acs.nanolett.7b02773
|View full text |Cite
|
Sign up to set email alerts
|

NanoVelcro: Theory of Guided Folding in Atomically Thin Sheets with Regions of Complementary Doping

Abstract: Folding has been commonly observed in two-dimensional materials such as graphene and monolayer transition metal dichalcogenides. Although interlayer coupling stabilizes these folds, it provides no control over the placement of the fold, let alone the final folded shape. Lacking nanoscale "fingers" to externally guide folding, control requires interactions engineered into the sheets that guide them toward a desired final folded structure. Here we provide a theoretical framework for a general methodology toward … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 101 publications
0
7
0
Order By: Relevance
“…Origami, the ancient art of paper folding, has been widely used in diverse areas, from architecture to battery design and DNA nanofabrication (10). It has also inspired the fabrication or simulation of macroscale origami graphene structures and devices (11)(12)(13)(14)(15)(16)(17)(18)(19)(20), even machines (21). Nano-scale graphene origami, however, in which quantum phenomena are expected to be manifest, has been mainly the realm of theoretical investigations, predicting GNSs with unusual physical properties such as an ability to carry spin-polarized currents for spintronic applications (22), foldinduced gauge fields (23), large permanent electric dipoles (24), strong magnetophotoelectric effect (25), and topologically protected fold states (26).…”
mentioning
confidence: 99%
“…Origami, the ancient art of paper folding, has been widely used in diverse areas, from architecture to battery design and DNA nanofabrication (10). It has also inspired the fabrication or simulation of macroscale origami graphene structures and devices (11)(12)(13)(14)(15)(16)(17)(18)(19)(20), even machines (21). Nano-scale graphene origami, however, in which quantum phenomena are expected to be manifest, has been mainly the realm of theoretical investigations, predicting GNSs with unusual physical properties such as an ability to carry spin-polarized currents for spintronic applications (22), foldinduced gauge fields (23), large permanent electric dipoles (24), strong magnetophotoelectric effect (25), and topologically protected fold states (26).…”
mentioning
confidence: 99%
“…[14] Previous studies reported that graphene could be folded by a contact-free atomic force microscope (AFM) tip [15] or scanning tunneling microscope (STM) tip. [16,17] In addition, graphene origami occurs with external stimuli such as temperature, [18][19][20] light, [21] strain, [2,22] doping, [23] solvent, [24] and also spontaneously due to the formation of joint edges in the growth process. [25] Chen et al realized the atomically precise and direction-controllable folding of graphene nano island (GNI) using an STM tip at ultra-low temperature.…”
Section: Introductionmentioning
confidence: 99%
“…It is a way of building 3D devices based on 2D materials. Thus, it has already stimulated the development of simulation and fabrication of folded graphene structures and devices [18][19][20][21][22][23][24][25][26][27], and origami machines [28]. Considerable effort devoted to achieving folded graphene structures can be traced back to 1995 by Ebbesen and Hiura, who were first envisioned 'Graphite origami', and they observed the folding of graphite surface layers with accidental tearing through an atomic force microscope tip [29].…”
Section: Introductionmentioning
confidence: 99%